Exploring teachers’ experiences on structural support programmes promoting teacher well-being in schools in rural settings - Dlhlamini, Masabata Anna (University of the Free State, 2024)
Exploring teachers’ well-being has emerged as a topic of profound significance in educational psychology globally and locally. This burgeoning area reflects a growing recognition of the pivotal role of teachers' welfare in shaping the quality of teaching and learning experiences within educational settings. Against the backdrop of the COVID-19 pandemic, which precipitated unprecedented challenges for educational systems worldwide, understanding and addressing the well-being of teachers has assumed heightened importance. This study explores the teachers' experiences in improving their well-being in rural high schools during COVID-19. This study adopted a qualitative approach through a phenomenological research design. It employed an interpretive paradigm. It used semi-structured interviews to collect data. These data were analysed through narrative analysis. The results suggested that teachers encountered multiple experiences with structural support programmes in rural schools. These included unawareness of the programmes, heavy workload, lack of support from SMT, insufficient time for family, unfair treatment from the management, lack of running water and electricity, undisciplined learners, and teachers’ absenteeism at rural schools. The results indicated that structural support programmes could help improve teachers’ well-being in rural schools. The results further revealed that support programmes could influence teachers’ well-being and job performance, especially on the teachers’ well-being. Research has suggested strategies for schools to reduce the number of overcrowded classrooms. However, information on how teachers in South Africa's rural schools might manage student overpopulation is lacking. Teachers’ resilience and self-efficacy could help them deal with challenges in the classroom. Furthermore, government officials advise adaptation when changing attitudes, behaviours, and feelings for the teachers’ well-being. Lastly, during the COVID-19 era 2019\2020, a South African department proposed that teaching be converted to an online format 2019–2020, during the COVID-19 pandemic. This recommendation was potentially convenient for teachers and learners. Nonetheless, teachers and other learners faced difficulties due to a shortage of resources.
Dissertation (M.Ed. (Psychology of Education))--University of the Free State, 2024
Keywords: Structural support programmes, Teachers’ self-efficacy, Teachers’ resilience, Teachers’ well-being, Rural schools, COVID-19